Une methode simple d'adaptation des maillages pour le calcul des ecoulements compressibles - Soulaimani, Azzedine; Chasse, Daniel; Lamarche, Louis (European Journal of Computational Mechanics, 1995)
This work presents some recent results on the solution of compressible flows using a simple adaptive mesh method and finite element code. This method consists of mesh enrichment and mesh derefinement procedures, and is based upon a special finite element residual norm. The residual norm provides a reliable indicator of regions to be adapted and hence to improve the quality of the solution. The paper presents the finite element formulation used, a modified Delaunay triangulation of arbitrary planar domains and the algorithms related to their adaptivity. Several numerical examples are presented which demonstrate the performance of our methods in solving compressible high speed flows.